Uniwersytet powszechny związków zawodowych. (Gdańsk : [wydawca nieznany], 1949)
Afisz informujący o zapisach.
Keywords: Szkoły -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła; Gdańsk (Polska) -- 1945-1970 -- życie intelektualne